A GIS-based Computational Tool for Multidimensional Flow Velocity by Acoustic Doppler Current Profilers. (May 2015) - Kim, D; Winkler, M; Muste, M
Abstract: Acoustic Doppler Current Profilers (ADCPs) provide efficient and reliable flow measurements compared to other tools for characteristics of the riverine environments. In addition to originally targeted discharge measurements, ADCPs are increasingly utilized to assess river flow characteristics. The newly developed VMS (Velocity Mapping Software) aims at providing an efficient process for quality assurance, mapping velocity vectors for visualization and facilitating comparison with physical and numerical model results. VMS was designed to provide efficient and smooth work flows for processing groups of transects. The software allows the user to select group of files and subsequently to conduct statistical and graphical quality assurance on the files as a group or individually as appropriate. VMS also enables spatial averaging in horizontal and vertical plane for ADCP data in a single or multiple transects over the same or consecutive cross sections. The analysis results are displayed in numerical and graphical formats.